Isolation, screening, and molecular identification of endopytic fungus producing cellulose and cyanide degrading enzyme its application for waste cassava. - Marlida, Yetti; Husmaini, Husmaini; Yuniza, Ahadiyah; Anggraini, Lili; Astut, Wulansih Dwi; Rusli, Ridho Kurniawan; Triani, Hera Dwi; Yant, Gusri (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This research aims to isolate, screen, and identify some candidates for endophytic fungus-producing cellulase and cyanidase. Materials and Methods: Fungi were isolated from cassava leaves that had undergone surface sterilization. The fungal isolates were qualitatively tested for their ability to produce cellulase and cyanidase enzymes by adding carboxy methyl cellulose (CMC) and KCN to the media. Enzyme production was indicated by the formation of clear zones around the growing colonies. Isolates that tested positive for cellulase and cyanidase production underwent further quantitative screening to measure enzyme activity using a spectrophotometer at wavelengths of 540 nm and 400 nm, respectively. The isolates showing the highest cellulase and cyanidase activity were identified through 18S rRNA analysis using the Sanger DNA sequencing method. Results: The research obtained six pure isolates of endophytic fungus, namely Y1; Y2; Y3; Y4; Y5; and Y6. Four isolates had the ability to degrade CMC with a clear zone between 0.1 until 0.5 mm, and three isolates had the ability for KCN degrade. The highest activity for cellulase and cyanidase degrading enzymes was produced by isolate Y2. After molecular identification using 18S rRNA, isolate Y2 had 98.82% similarity to Phomopsis sp. 32PG/F. Conclusion: Six isolates of endophytic fungi were obtained, Y1; Y2; Y3; Y4; Y5; and Y6. Four isolate the ability of to degrade CMC and three isolate the ability for KCN degrade. Isolate Y2 is the isolate with the best activity for cellulase and cyanidase degrading enzymes, namely 2.99 U/ml and 2.19 U/ml. After molecular identification using 18S rRNA, isolate Y2 had 98.82% similarity to Phomopsis sp. 32PG/F. J. Adv. Vet. Anim. Res., 12(1): 169–178, March 2025 http://doi.org/10.5455/javar.2025.l884